2015
DOI: 10.31768/2312-8852.2015.37(1):64-69
|View full text |Cite
|
Sign up to set email alerts
|

The Immunophenotype of Adult T Acute Lymphoblastic Leukemia in Morocco

Abstract: Background: There is paucity of detailed studies of adult T cell acute lymphoblastic leukemia (T-ALL) in developing countries reflecting the condition of these patients including clinical and biological features. Objective: This study was carried out to analyze the immunophenotypic characteristics of 40 Moroccan patients with T-ALL and its association with biological and clinical features. Patients and Methods: Between 2006 and 2009, 130 adult patients diagnosed with acute lymphoblastic leukemia (ALL) were imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
2
8
2
Order By: Relevance
“…Our figures for the proportion of B‐ALL and T‐ALL at 85.5%, and 14.5% are virtually identical to the 84.5% and 15.6% reported by the Middle East Childhood Cancer Alliance in 2014 . It is also consistent with most studies worldwide . Moreover, our relative rates of 88% for the common B‐ALL and 73.2% for cortical T‐ALL subtypes were within the ranges for these two subtypes reported worldwide at 67.2%‐90% and 31.5%‐80.4%, respectively …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our figures for the proportion of B‐ALL and T‐ALL at 85.5%, and 14.5% are virtually identical to the 84.5% and 15.6% reported by the Middle East Childhood Cancer Alliance in 2014 . It is also consistent with most studies worldwide . Moreover, our relative rates of 88% for the common B‐ALL and 73.2% for cortical T‐ALL subtypes were within the ranges for these two subtypes reported worldwide at 67.2%‐90% and 31.5%‐80.4%, respectively …”
Section: Discussionsupporting
confidence: 89%
“…With regard to cross‐lineage antigens expression in T‐ALL, B‐cell antigen expression (cCD79a) constituted around a quarter of LAIP detected. CD79a was also noted as a frequent LAIP in some studies, while others documented CD19 as the most frequent B‐cell marker aberrancy in their T‐ALL . On the other hand, the frequency of myeloid antigens expression in T‐ALL was 7.3% in the current series.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…CD1a was positive in a little more than half of all cases (51.43%). A study in Moroccan children by Lahjouji et al found an excess of the common thymocyte subtype (80.4%) displaying reactivity with CD1a as compared with the frequency reported by others [8].…”
mentioning
confidence: 74%
“…In the past, it was believed that the prognosis of ALL showing expression of myeloid antigen (Mye(+)ALL) was poorer than that of ALL with no myeloid antigen expression (Mye(–)ALL). However, recent papers suggested that there was no significant difference ­between the prognosis of these 2 groups (22–23–25). As previously mentioned, our 3 cases were different from those described in other reports.…”
Section: Discussionmentioning
confidence: 97%